2005
DOI: 10.1520/jte11981
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Investigate the Influence of Soil Properties on Suction

Abstract: Various models that incorporate the influence of soil suction on different engineering properties of unsaturated soils have been developed. However, a systematic study of various physical parameters of the soil mass such as type of soil, particle size distribution, and the state of compaction (i.e., water content, dry unit weight, and saturation) is required to understand the influence of these parameters on soil suction, directly or indirectly. This would be of great help in understanding the unsaturated prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…This fitting function is widely used in the literature and has been formulated based on the more realistic pore size distribution of (Fredlund and Xing, 1994;Miller et al, 2002;Singh and Kuriyan, 2002;Sreedeep and Singh, 2005).…”
Section: Establishment Of the Soil-water Characteristic Curvementioning
confidence: 99%
See 1 more Smart Citation
“…This fitting function is widely used in the literature and has been formulated based on the more realistic pore size distribution of (Fredlund and Xing, 1994;Miller et al, 2002;Singh and Kuriyan, 2002;Sreedeep and Singh, 2005).…”
Section: Establishment Of the Soil-water Characteristic Curvementioning
confidence: 99%
“…It must be noted that most of the methods that are reported in the literature (Fredlund and Rahardjo, 1993;Lee and Wray, 1995;ASTM D 3152;ASTM D 5298;ASTM D 6836;Sreedeep and Singh, 2005) for measuring soil suction are capable of yielding w m . On the other hand, w of the soil has been measured using a transistor or thermocouple psychrometers (Richards and Ogata, 1961), filter papers (Leong et al, 2002) and a dew point potentiameter (WP4) (Leong et al, 2003;Thakur et al, 2005a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Since the experimental procedures adopted for determining the soil-suction-water-content relationship are time consuming and cost intensive, recent research has placed a major focus on indirect estimations of the SWCC. Whereas the shape of the curve depends on many basic soil properties, such as the type, size, and shape of the minerals in the soil's composition, and on the environmentally induced factors that determine the fabric, porespace geometry, and void ratio of soils, as well as the chemical composition of the pore water (Sreedeep and Singh 2005), it is difficult to find a generally valid mathematical expression to describe it. However, several analytical functions for predicting the SWCC can be found in the literature (Ross et al 1991;Kosugi 1994;Rossi and Nimmo 1994;Or and Tuller 1999;Fayer and Simmons 1995;Groenevelt and Grant 2004;Tuller and Or 2005;Khlosi et al 2006;Thakur et al 2006;Frydman and Baker 2009;Chin et al 2010;Salager et al 2010;Sreedeep and Singh 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The uniqueness of the soil water retention curve, SWRC, has been studied by earlier researchers and it has been reported that it gets influenced by various factors such as the soil type (Fredlund et al 2002, Pham et al 2005, Frydman and Baker 2009, Noh et al 2011, water F o r P e e r R e v i e w O n l y content and compaction efforts (Tinjum et al 1997, Vanapalli et al 1998, 1999Pang 2000a, 2000b;Miller et al 2002, Sreedeep and Singh 2005, Thakur et al 2005, 2006, initial void ratio (Kawai et al 2000), stress history (Delage and Lefebvre 1984, Vanapalli et al 1998, 1999Pang 2000a, 2000b;Marinho 2005), and the path viz., drying-or wetting-path, adopted to achieve it (Likos and Lu 2002, Yang et al 2004, Pham et al 2005, Agus and Schanz 2006, Konyai et al 2006, Mohammed and Sharma 2007, Fredlund et al 2011, Jayanth et al 2012. Incidentally, earlier studies have also noted the effect of initial state of soil (intact, slurried or compacted) on its SWRC (Fredlund et al, 2002;Pham et al, 2008).…”
Section: Introductionmentioning
confidence: 99%